Financial Attitude, Financial Knowledge, and Income on Muhammadiyah University of Gresik’s Management Students’ Financial Behavior - Anggraini, Novita; Santoso, Rahmat Agus; Handayani, Anita; Rizqi, Maulidyah Amalina (International Journal Labs, 2022)
Financial behavior is the ability to manage, plan, budget, manage, and save money in life. The results of the pre-survey conducted by researchers showed that university of Muhammadiyah Gresik management students in 2018-2020 were still unable to manage finances properly. This research aims to find out the influence of Financial Attitude, Financial Knowledge, and Income on Financial Behavior on University of Muhammadiyah Gresik Management Students. The research method used quantitative research methods with a sample of 257 respondents. The data obtained is analyzed with multiple linear regression analysis techniques using the SPSS 20 program. The results showed that financial attitude has a positive and significant effect on financial behavior, financial knowledge has a positive and significant effect on financial behavior, and income has a positive and significant effect on financial behavior.